Preparing method of carbon layer coated foam copper composite material and method for auxiliary brazing of C/C composite material and metal - XIAO HAIYING; QIU SI; ZHANG DONGXING; LI MANNI; ZHENG TING; LIU YINGYI; LU CHUNRUI (2017)
The invention discloses a preparing method of a carbon layer coated foam copper composite material and a method for auxiliary brazing of a C/C composite material and metal, and belongs to the technical field of a polymer-matrix composite material and welding. The problem that during existing brazing of the C/C composite material and the metal, large residual stress exists in an after-welding joint, and the strength of the joint is seriously weakened is solved. According to the preparing method of the composite material, foam copper is placed in an acetone solution of the polymer, magnetic stirring is carried out, and after the foam copper is taken out, the copper is subject to vacuum drying; tubular furnace interior sintering is carried out, and cooling to the room temperature is achieved; according to the brazing method, the carbon layer coated foam copper composite material prepared through the method is clamped between silver copper titanium alloy brazing foil pieces, and then is placed between the metal a